Psychological Social Behavior: Taxable Entrepreneurs Respond to Vat Policy Changes - Wibowo, Danny (Future Science, 2024)
Environmental considerations or individual intentions influence taxpayer behavior. VAT changes may be a reaction to behavior either overtly or covertly. This research applies an approach approach with the method of interviews conducted with business actors. However, VAT can reduce profits by influencing consumers to spend resources and look for lower prices. Regarding the VAT rate, it is still considered unfair. Furthermore, double recording or splitting the business into several forms is implemented, which is passed on to other family members. Another option is to do tax planning to meet the tax burden. Decisions in the information action model can be based on rationality, routine behavior, nature/tradition and subjective norms / perceptual behavior. Findings from an environmental perspective are formed from the level of experience and age, as well as the encouragement of social communities and provide psychological stimuli for taxpayer behavior in assessing changes in tax regulations, especially about VAT rates.